Effects of Drought Stress on the Relationship Between Solar-Induced Chlorophyll Fluorescence and Gross Primary Productivity in a Chinese Cork Oak Plantation - Qingmei Pan; Chunxia He; Shoujia Sun; Jinsong Zhang; Xiangfen Cheng; Meijun Hu; Xin Wang (Remote Sensing)
Solar-induced chlorophyll fluorescence (SIF) is a powerful tool for the estimation of gross primary productivity (GPP), but the relationship between SIF and GPP under drought stress remains incompletely understood. Elucidating the response of the relationship between SIF and GPP to drought stress is essential in order to enhance the precision of GPP estimation in forests. In this study, we obtained SIF in the red (SIF687) and far-red (SIF760) bands and GPP data from tower flux observations in a Chinese cork oak plantation to explore the response of the diurnal GPP-SIF relationship to drought stress. The plant water stress index (PWSI) was used to quantify drought stress. The results show that drought reduced SIF and GPP, but GPP was more sensitive to drought stress than SIF. The diurnal non-linear relationship of GPP-SIF (R2) decreased with the increase in drought stress, but a significant non-linear correlation remained for GPP-SIF (R2_GPP-SIF760 = 0.30, R2_GPP-SIF687 = 0.23) under severe drought stress (PWSIbin: 0.8–0.9). Physiological coupling strengthened the GPP-SIF relationship under drought, while canopy structure effects were negligible. Random forest and path analyses revealed that VPD was the key factor reducing the GPP-SIF correlation during drought. Incorporating VPD into the GPP-SIF relationship improved the GPP estimation accuracy by over 48% under severe drought stress. The red SIF allowed for more accurate GPP estimations than the far-red SIF under drought conditions. Our results offer important perspectives on the GPP-SIF relationship under drought conditions, potentially helping to improve GPP model predictions in the face of climate change.